Emotional Branding and Customer Loyalty: Gen Z in Japan and Indonesia - Isroni Isroni; Dedi Suharyadi; Sukmono Bayu Adhi; Roy Irawan (International Journal of Economics and Management Research, 2025)
Global brands increasingly struggle to retain Generation Z consumers who demand emotionally resonant and culturally relevant brand experiences. In Japan, where emotional restraint and symbolic messaging dominate consumer-brand interactions, Gen Z tends to bond with brands through aesthetics, storytelling, and quiet symbolism. Meanwhile, in Indonesia, Gen Z consumers exhibit high emotional expressiveness and loyalty to brands that foster social connection, authenticity, and community engagement. This paper analyzes how emotional branding mechanisms—such as brand love, emotional attachment, and self-congruity—function differently across these cultural settings. It reveals that while Japanese Gen Z responds to minimalist branding with embedded cultural cues, their Indonesian counterparts engage more with emotionally charged narratives and influencer-driven content. These distinctions offer practical insights for tailoring emotional branding to fit not only cultural norms but also platform-specific behaviors, such as Instagram aesthetics in Japan and TikTok virality in Indonesia. The study contributes actionable strategies for brands aiming to sustain loyalty among Gen Z in culturally diverse Asian markets.